PENGARUH TRANSPORTASI JARAK PENDEK TERHADAP LEVEL HORMONTRIIODOTIRONIN (T3) DARAH KAMBING PERANAKAN ETTAWA - , DYAH HAPSARI EKA N; , drh. Claude Mona Airin, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Transportation is an important aspect marketing process in the livestock. Transport can cause stress for animal due to the treatment during transport, which can cause metabolic disorders leading to weight loss after transportation, reduction in meat quality, increased mortality and physiological disturbances. The aim of this study was to determine the effect of short term transportation to the blood triiodothyronine (T3) hormone level in Ettawa-crossbreed. This study conducted using five female Ettawa-crossbreed goats. The all treated goats had the same age and kept in healthy physically. These goats were transported 35 km from Girimulyo towards Nanggulan with an average speed of 35 km/h. Blood sampling was done three times: before transport, after transport, and seven days after transport. The levels of T3 was determined using in ELISA technique. The data was analyzed using analysis of variance (ANOVA) one-way followed by the Tukey test. The result showed that at the time before transport T3 levels was 1,04 ± 0,32 ng/ml, after transport was 0,85 ± 0,59 ng/ml, and seven days after transport was 1,79 ± 0,44 ng/ml. The results showed a decrease in T3 hormone levels after transport and T3 hormone levels were increase seven days after transport. The levels of T3 was significantly different (P<0,05) compared with after transport and seven days after transport. It means that the transportation short term of the T3 levels did not cause the changes T3 levels. Triiodothyronine hormone levels before transport and after transport was not different (P>0,05) could be due to transportation performed for an hour did not affect the changes in hormone T3.